Growing Heirloom Tomato Varieties in Southwest Florida - Charles S. Vavrina; Karen Armbrester; Michiko Pena (EDIS, 2003)
This document is Fact Sheet HS921, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultual Sciences, University of Florida. Original publication date: April 2003.